Vertebrate trace fossils and environments of the Yacoraite Formation (Maastrichtian-Danian). New records from the Valle del Tonco tracksite, northwestern Argentina - Cónsole Gonella, Carlos Alfredo (2015)
Fil: Cónsole Gonella, Carlos Alfredo. CONICET-Instituto Superior de Correlación Geológica (INSUGEO); Argentina.